Learning and Teaching Islamic Economics: Bridging Academic Knowledge and Professional Practice in the Sharia Financial Industry - Mohamad Heri Hadian; Iin Indra Nuraeni; Neni Utami Adiningsih; Reni Marlina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid expansion of the Sharia financial industry has intensified the need for graduates who are not only grounded in the epistemological foundations of Islamic Economics but also equipped with professional competencies relevant to contemporary financial practices. Despite significant growth in Islamic finance, a persistent gap remains between academic instruction and industry expectations, particularly in areas of applied analytical skills, curriculum responsiveness, and institutional collaboration. This study explores how learning and teaching in Islamic Economics can more effectively bridge academic knowledge and professional practice. Employing a qualitative exploratory approach, data were gathered through in-depth interviews and document analysis involving academic stakeholders and industry-related informants. Thematic analysis identified six interconnected dimensions influencing educational effectiveness: integration between economic theory and fiqh al-muamalat, competency-oriented curriculum alignment, experiential and practice-based pedagogy, balanced institutional governance, strategic industry partnerships, and data-informed quality enhancement. The findings indicate that fragmented instructional design, limited experiential exposure, and structural workload constraints hinder the preparation of industry-ready graduates. Conversely, coherent epistemological integration and sustained collaboration with industry actors enhance both professional readiness and adherence to Sharia principles. The study underscores the importance of systemic transformation rather than incremental reform, emphasizing the need for adaptive curricula, immersive learning environments, and collaborative knowledge ecosystems. Strengthening these dimensions is essential to ensure that Islamic Economics education remains ethically grounded, professionally relevant, and capable of responding to ongoing innovation within the global Sharia financial landscape.